5‐aminosalicylate maintenance is not superior to no maintenance in patients with newly diagnosed Crohn's disease—A nationwide cohort study. Issue 9 (9th March 2023) - Atia, Ohad; Goren, Idan; Fischler, Tali Sharar; Weisband, Yisca Loewenberg; Greenfeld, Shira; Kariv, Revital; Ledderman, Natan; Matz, Eran; Rimon, Ramit Magen; Dotan, Iris; Turner, Dan; Yanai, Henit
Summary: Background: 5‐aminosalicylates (5‐ASA) are widely used in Crohn's disease (CD) despite guidelines advising otherwise. We aimed to assess in nationwide study the outcomes of first‐line 5‐ASA maintenance therapy (5‐ASA‐MT) compared with no maintenance treatment (no‐MT) in patients with newly diagnosed CD. Methods: We utilised data from the epi‐IIRN cohort, including all patients with CD diagnosed in Israel between 2005 and 2020. Propensity score (PS) matching was utilised to compare outcomes in the 5‐ASA‐MT versus no‐MT groups. Results: Of the 19, 264 patients diagnosed with CD, 8610 (45%) fulfilled the eligibility criteria (3027 [16%] received 5‐ASA‐MT and 5583 [29%] received no‐MT). Both strategies declined over the years; 5‐ASA‐MT from 21% of CD patients diagnosed in 2005 to 11% in 2019 ( p < 0.001) and no‐MT from 36% to 23% ( p < 0.001). The probability of maintaining therapy at 1, 3 and 5 years from diagnosis: 5‐ASA‐MT—78%, 57% and 47% and no‐MT—76%, 49% and 38% respectively ( p < 0.001). PS analysis successfully matched 1993 pairs of treated and untreated patients and demonstrated comparable outcomes of time to: biologic ( p = 0.2), steroid dependency ( p = 0.9), hospitalisation ( p = 0.5) and CD‐related surgery ( p = 0.1). Rates of acute kidney injury (5.2% vs. 3.3%; p < 0.001) and pancreatitis (2.4% vs. 1.8%; p = 0.03) were higher in the 5‐ASA‐MT group compared with the no‐MT group but after PS matching the rates of adverse events were similar. Conclusion: First‐line 5‐ASA monotherapy was not superior to no‐MT but associated with a slightly higher rates of adverse events, while both strategies have declined over the years. These findings suggest that a subset of patients with mild CD may be offered a watchful waiting approach. Abstract :